Inhibition of Hepatitis B Virus Replication during Adenovirus and Cytomegalovirus Infections in Transgenic Mice - Cavanaugh, Victoria J. (American Society for Microbiology, 1998)
We have previously demonstrated that hepatitis B virus (HBV) replication and gene expression are abolished in the livers of HBV transgenic mice by cytotoxic T lymphocytes (CTLs) and during lymphocytic choriomeningitis virus (LCMV) infection, stimuli that trigger the production of alpha/beta interferon, gamma interferon, and tumor necrosis factor alpha in the liver. We now report that hepatic HBV replication and gene expression are inhibited by the local induction of these cytokines during adenovirus- and murine cytomegalovirus (MCMV)-induced hepatitis. Further, we show that MCMV also blocks HBV replication and gene expression in the proximal convoluted tubules of the kidney by causing interstitial nephritis and inducing the same cytokines in the renal parenchyma. These results suggest that inflammatory cytokines probably contribute to viral clearance during acute viral hepatitis in humans, and they imply that induction of these cytokines in the liver and other infected tissues of chronically infected patients might have therapeutic value.